The Category of Ugliness in "Historie maniaków" by Roman Jaworski - Sikorska, Magdalena (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2020)
The article undertakes to interpret the collection of short stories titled Historie maniaków by Roman Jaworski using the category of ugliness. So far, this work has been analysed through a different aesthetic category, namely the grotesque, while the author himself drew attention in the discussed collection of short stories to ugliness and recommended that it should be chosen as the principle perspective. The analysis focuses on the impact of the ugliness category on the shaping of elements of the world presented in the work: the creation of the characters and their corporeality, settings, as well as the very composition of the collection and the construction of the language used by the author. The paper finishes with an attempt to interpret Historie maniaków using contemporary humanistic theories, which consider the category of ugliness as a positive value.